KAJIAN PENGOLAHAN SAMPAH ORGANIK DENGANBSF (Black Soldier Fly) di TPA Kebon Kongok - Ranncak, Gendewa Tunas; Alawiyah, Tuty; Hadi, Taufikul (Jurnal Ilmiah IKIP Mataram, 2018)
In this study a study was conducted regarding the processing of organic waste with the Black Soldier Fly (BSF) at the Kebon Kongok landfill. Kebon kongok is one of the Regional Landfill located in Suka Makmur Village, Gerung District, West Lombok Regency. There are ten management activities carried out at the Kebon Kongok landfill, namely weighing, landfill supervisors, heavy equipment operations, recycling, leachate management, gas handling (biogas), buffer zones, scavenger, social and organic waste processing with Black Soldier Fly (BSF ) The results of the study related to the study of processing organic waste with the Black Soldier Fly (BSF) showed that the stages in the processing of organic waste with BSF were weighing garbage, demolition of garbage in the unloading unit of waste (sorting process), enumeration of organic waste, weighing before being inserted into the bioreactor, the process in the bioreactor, the stage of harvesting the adult larvae, the removal of larval eggs into the hatcery, the transfer of BSF eggs to the hatcery, the transfer of larvae to the bioreactor to process organic waste, the larval breeding into flies to adulthood